DIGITALISASI PELAYANAN ADMINISTRASI TINGKAT LOKAL: EVALUASI IMPLEMENTASI E-RTNEM DI RT 06 RW 02 KELURAHAN BULAK SURABAYA - Linda Wuri Kusumaning Pratiwi; Nailul Ulah Al-Chumairah Machfud (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to describe the implementation of digital innovation in public services through the E-RTNEM application in RT 06 RW 02, Bulak Village, Surabaya, and to identify the supporting and inhibiting factors as well as its impact on service effectiveness. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with six informants, participant observation, and documentation. Data were analyzed using the Miles and Huberman interactive analysis model, while data validity was ensured through source, technique, and time triangulation. The findings indicate that the implementation of E-RTNEM was carried out systematically through the stages of planning, socialization, implementation, and evaluation. The application significantly improved service efficiency by reducing the processing time for administrative letters from one to two days to less than 30 minutes, while also enhancing accessibility, transparency, and cost efficiency. Supporting factors included the leadership of the neighborhood head, collaboration with university students, and community support. The main challenges were limited internet infrastructure, low digital literacy among older residents, resistance to change, and the limited availability of RT administrators.